Workload, interpersonal conflict, and work family conflict of events work stress on women workers sewing part - Tunika, Puriwati; Rahmani, Noor Siti; Surono, Agus (BKM Public Health and Community Medicine, 2021)
Purpose: Stress is a global epidemic. In the decade, more than 50% of the population in many countries reported experiencing work-related stress. The percentage of female workers working in the formal sector in Indonesia has increased every year, and female workers tend to be more vulnerable to work stress. Some of the causes of work stress in the industrial world are workload, interpersonal conflict, and work-family conflict. Methods: This study employed a quantitative cross-sectional design. The research sample was 70 respondents. This research utilized the National Institute of Occupational Safety and Health's Generic Job Stress Questionnaire as a measurement tool. Results: Results of chi-square and Fisher's exact test showed a positive correlation between workload (p = 0.00), interpersonal conflict (p = 0.00), and work-family conflict (p = 0.00) with work stress. The results of the logistic regression test showed that conflicts between interpersonal and work-family conflict correlated significantly with work stress, with a Pseudo R² value of 0.3285, indicating that the variables of interpersonal conflict and work-family conflict correlate equally to 32.85% of work stress. While 0.6715, or 67.15%, of work stress on women workers sewing parts may be caused by other factors. Conclusions: Workload, interpersonal conflict, and work-family conflict have a positive relationship with events and work stress on women workers sewing part.